Primary and Triage Cervical Screening Diagnostic Value of Methods for the Detection of Cervical Dysplasia. (17th September 2022) - Njue, James Kinoti; Muturi, Margaret; Kamau, Lucy; Lwembe, Raphael
Abstract : Background . Cervical cancer is a leading cause of mortality among women globally. Approaches to reduce cervical cancer incidence and mortality are "screen-and-treat, " where positive primary test only is used in the treatment and "screen, triage and treat, " where treatment is based on positive primary and triage tests with/without histological analysis. Objectives . To determine cervical screening outcomes among HIV-infected and noninfected women using VIA, Pap smear, and HPV-PCR cervical screening methods and to determine the sensitivity, specificity, PPV and NPV of VIA, Pap smear, and HPV-PCR as primary test and sequential triage based on abnormal histopathology among HIV-infected and noninfected women. Methodology . This was a comparative cross-sectional study where women aged 18-46 years women underwent cervical screening and colposcopy-biopsy test as a positive-confirmatory test in the Referral Hospitals of Eastern Kenya. Results . A total of 317 (HIV negative: 156/317 (49.2%) and HIV positive: 161/317 (50.8%)) women were enrolled. Of these 81/317 (25.6%), 84/317 (26.5%), 96/317 (30.2%), and 78/122 (63.9%) participants had VIA, HPV DNA-PCR, Pap smear, and cervical histology positive results, respectively; average: 27.4% (HIV positive: 21.5%; HIV negative: 5.9%). Majority of women with LSIL [17/317 (5.4%)], HSIL [22/317 (6.9%)], invasive cancer [5/317 (1.6%)], cervicitis [45/317 (14.2%], and candidiasis 47/317 (14.8%) were HIV-infected (p < 0.001 ). 78/317 (24.6%) participants had positive histology test [ASCUS: 34/317 (10.7%) CIN1:17/317 (5.3%), CIN2: 16/317 (5.0%), CIN3:6/317 (1.9%), and ICC: 5/317 (1.6%)] (p > 0.001 ). A higher primary diagnostic accuracy was established by HPV DNA-PCR (sensitivity: 95.5%; specificity: 92.6%) than Pap smear and VIA test while in triage testing, high sensitivity was obtained by HPV DNA-PCR parallel testing with VIA test (92.6%) and Pap smear test (92.7%) and VIA cotesting with Pap smear (99.9%). HIV-infected women had increased specificity and reduced sensitivity and diagnostic accuracy by both primary and triage testing approaches. Discussion . Abnormal cervical screening outcome was high among HIV-infected than noninfected women. HIV-infected women had significantly high cases of cervical neoplastic changes. The diagnostic value of primary tests increased upon concurrent testing with other test methods hence reducing the number of women who would have been referred for biopsy. Conclusion . High sensitivity and specificity in detection of CIN+ were established among HIV-infected than HIV noninfected women by HPV DNA-PCR and Pap smear than VIA test. HPV DNA-PCR test and Pap smear are more accurate in primary and sequential triage cervical screening based on abnormal histopathology outcomes among HIV-infected than noninfected women.